Design of A Ballast Tank For A Small Underwater Remotely Operated Vehicle (ROV) - Mohd Ubaidillah bin Mohd Kamal, Mohd Ubaidillah (Universiti Teknologi PETRONAS, 2008)
Underwater Remote Operated Vehicle is tethered marine robots that are widely used in oil and gas industry. Underwater vehicles such as ROVs operate while tethered to a surface ship, and must be able to surface and submerge, thus requiring dynamic buoyancy control. ROVs also require dynamic buoyancy control for its own stability and depth control. The dynamic buoyancy can be applied by using Ballast Tank. This project works involves designing and analysis of Ballast Tank for small, lightweight, open frame and low cost underwater Remotely Operated Vehicle (ROV). This system should be 2 Degree of Freedom (DOF); Yaw and Heave. The analysis and calculation have be done to determine the required size of ballast tank, its’ system, durability and the strength. The materials for Chassis and Ballast tank have been selected by considering the requirement. The tank has been design with several considerations. The 3D-drawing, detail drawing, assembly drawing and analysis of the tank have been done by using CATIA software.